Autumn morning flights of migrant songbirds in the northeastern United States are linked to nocturnal migration and winds aloft. (12th November 2014) - Van Doren, Benjamin M.; Sheldon, Daniel; Geevarghese, Jeffrey; Hochachka, Wesley M.; Farnsworth, Andrew
Abstract: Many passerines that typically migrate at night also engage in migratory flights just after sunrise. These widely observed "morning flights" often involve birds flying in directions other than those aimed toward their ultimate destinations, especially in coastal areas. Morning flights have received little formal investigation, and their study may improve our understanding of how birds orient themselves during and after nocturnal movements and how they use stopover habitat. We studied autumn morning flights in the northeastern United States to identify associations between the number of birds undertaking morning flights and the magnitude of nocturnal migratory movements, nocturnal winds, and local topography. Our analyses included observations of more than 15, 000 passerines at 7 locations. We found positive relationships between morning flight size and nocturnal migration density and winds aloft: Significantly more birds flew following larger nocturnal movements, quantified from weather surveillance radar and recordings of nocturnal flight calls, and after stronger nocturnal crosswinds. We also found consistent differences in morning flight size and direction among sites. These patterns are consistent with migrants engaging in morning flight as a corrective measure following displacement by nocturnal winds and to search for suitable stopover habitat.